Evaluating the tensile strength of friction welded (AA6061 & AA7075-T6) dissimilar joints by using response surface methodology. (8th May 2019) - Bakkiyaraj, M; Palanisamy, P; Balasubramanian
Abstract: This paper aims at formulating a numerical model to predict and optimize the friction welding (FW) process parameters on the tensile strength of the dissimilar, (AA6061/AA7075-T6) aluminium alloy joints. The ultimate tensile strength of friction welded dissimilar joints can be obtained by varying the FW parameters within the process windows. The response surface methodology (RSM) was identified as the method for optimizing the FW process parameters to maximize the tensile strength of dissimilar joints and the optimized parameters were accounted. Finally, the characterization of specimens at the weld zone was studied by using scanning electron microscope (SEM), energy-dispersive spectroscopy (EDS) and optical microscope (OM).